The dilemma of the democratic State in Africa - SIMAO NHAMBI (African Journal of Governance and Development, 2014)
This edition comes out at a time when in the latest general election held on 15 October, Mozambique made history by electing the first president who has not been directly involved in the war of liberation. After Samora Machel, Joaquim Chissano and Armando Guebuza, Filipe Jacinto Nyusi will become the country’s fourth president. The election of Filipe Nyusi opens a way for him to lead the historic ruling party, Frelimo.While one can look at the election of the new president of Mozambique as a simple democratic process, it should be noted that the dynamic of the democratic state imposes the need of leadership to be more innovative and outreaching and to develop economic and social policies to meet the demands of the masses. The greatest challenge that any leadership, in Africa, face (Mozambique is not an exception) is the ability to maintain peace and political stability as well as the ability to develop and implement social and economic policies that are inclusive and responsive to the short, medium and long term needs of the country.